The Efficacy of Radiofrequency in Tonsillectomy Procedures: A Comprehensive Systematic Review - Anika Istika; Revy Octarian Palmendha (The International Journal of Medical Science and Health Research, 2025)
Background: Tonsillectomy, a common surgical procedure, has seen advancements in radiofrequency (RF) technology, aiming to improve postoperative outcomes by reducing intraoperative bleeding, postoperative pain, and recovery time. However, the efficacy of RF in tonsillectomy remains a topic of ongoing research, requiring further evaluation for optimal patient care. Methods: This systematic review adhered to PRISMA 2020 principles and focused exclusively on full-text papers published in English between 2015 and 2025.   Editorials and review articles without a DOI were omitted to preserve the integrity of high-quality sources.   A literature review was conducted utilizing esteemed databases like ScienceDirect, PubMed, and SagePub to discover relevant studies. Result: The preliminary database search yielded over 500 relevant publications on the topic. Following a comprehensive three-stage screening process, eight papers met the specified inclusion criteria and were selected for in-depth analysis. Each study underwent a comprehensive critical assessment, enabling a thorough understanding of the efficacy of radiofrequency in tonsillectomy procedures. This methodical method guaranteed that the analysis relied on high-quality evidence, corresponded with the study's aims, and was capable of producing substantial insights into this intricate relationship. Conclusion: Radiofrequency tonsillectomy is a surgical technique that enhances postoperative comfort, reduces risks, and supports faster return to normal activity. However, long-term outcomes and recurrence rates require further exploration. Standardized protocols for radiofrequency tonsillectomy are essential for improving patient outcomes and redefining otolaryngologic surgery standards.